2013
DOI: 10.1007/s10096-013-1825-9
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection in acute gastroenteritis predicts a more severe clinical course in children

Abstract: The objectives of this study were to determine the incidence of enteric pathogens causing acute gastroenteritis (AGE) among hospitalized children in a large Italian hospital, to measure the incidence of coinfections, and to compare the clinical characteristics of those infected with one versus multiple agents. A prospective study was conducted from March 2010 to April 2011 at the Bambino Gesù Pediatric Hospital in Rome, Italy. All patients between 1 month and 16 years of age admitted to the Pediatric Departmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
52
3
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 35 publications
14
52
3
6
Order By: Relevance
“…Although a singlecenter study reported a 11% rate of C difficile coinfection among pediatric cases, most of the coinfected cases were ,1 year of age. 33 The distribution of NAP types in our study was consistent with recent US findings among adults with CA CDI, in whom NAP1 was the most common strain type. 26 The predominance of the NAP1 strain among CA pediatric cases is notable, because 1 factor postulated to have contributed to its emergence is high-level resistance to fluoroquinolones.…”
Section: Figuresupporting
confidence: 91%
“…Although a singlecenter study reported a 11% rate of C difficile coinfection among pediatric cases, most of the coinfected cases were ,1 year of age. 33 The distribution of NAP types in our study was consistent with recent US findings among adults with CA CDI, in whom NAP1 was the most common strain type. 26 The predominance of the NAP1 strain among CA pediatric cases is notable, because 1 factor postulated to have contributed to its emergence is high-level resistance to fluoroquinolones.…”
Section: Figuresupporting
confidence: 91%
“…Studies included children aged 0-2 years (n=4), 0-5 years (n=2), 0-12 years (n=3) and 0-18 years (n= 22). The majority of studies were from North America (n=12; 6,184 cases) [13][14][15][16][17][18][19][20][21][22][23][24] and Europe (n=12; 2,467 cases) [8,[25][26][27][28][29][30][31][32][33][34][35], with other studies from Asia (n=4; 1,762 cases) [36][37][38][39], Australia (n=2; 148 cases) [40,41] and South America (n = 1; 210 cases) [42]. Ten studies included only community-onset patients [13,14,25,27,28,31,32,34,35,38], three included only hospital patients [20,30,40], 12 included both hospital and community [8, 15, 16, 19, 21-24, 26, 29, 33, 42] and six studies did not report the place of onset [17,…”
Section: Studies Included In the Analysismentioning
confidence: 99%
“…Albert et al analysed stool samples from 814 children with diarrhoea (aged 0-5 years), noting a coinfection in 53.8 % (7/13) of those with a positive C. difficile test (rotavirus, n=2; C. jejuni, n=1, enteropathogenic E. coli, n=1, enterotoxigenic E. coli, n=1, Aeromonas spp., n=1; Shigella spp., n=1) [37]. Twenty studies tested for bacterial co-infection in all samples [13,18,19,23,24,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], 13 tested for viral pathogens (of which five tested for rotavirus only) [16, 18, 19, 23, 27-31, 33-35, 37] and six tested for parasites [23,30,32,33,37,40]. In ten studies, not all samples were tested for co-infection or no data were reported on the number of tested samples [8, 14, 15, 17, 20-22, 25, 26, 42].…”
Section: Rate Of C Difficile Co-infection With Other Gastrointestinamentioning
confidence: 99%
“…These viruses commonly infect young children, often without signs of clinical disease (67)(68)(69)(70)(71). Coinfections involving RV and other enteric viral or bacterial pathogens have been frequently reported, and there have been a few studies suggesting that coinfections with certain pathogens can alter GI disease severity (63,(72)(73)(74)(75)(76). However, little information is available concerning whether coinfection of young children, and particularly neonates, with RV and Aichi virus, astrovirus, or salivirus/klassevirus has an impact on disease symptoms.…”
Section: Discussionmentioning
confidence: 99%